PERBANDINGAN TINGKAT KEAWETAN KAYU SENGON (Falcataria moluccana L. Nielsen) DAN KAYU SUGI (Cryptomeria japonica D. Don) DENGAN EKSTRAK LIMBAH KULIT KAYU JATI (Tectona grandis L.F.) TERHADAP SERANGAN RAYAP TANAH Coptotermes curvignathus Holmgren - Nofi Utari; Farah Diba; Lolyta Sisillia (Universitas Tanjungpura, 2018)
The aim of the study was to obtain a comparison of the durability of sengon (Falcataria moluccana) and sugi wood (Cryptomeria japonica) after preservation with Jati (Tectona grandis) tree bark waste to subterranean termites Coptotermes curvignathus Holmgren attack and to determine the best concentration of wood preservation from Jati extract. Evaluation the durability of wood used the JIS K 1571 2004 standar method. Test parameters in the study were preservative retention, termite mortality and weight loss of the wood test sample. The results showed the highest retention was achieved in Sengon wood of 0.466 kg /m3 and the followed by Sugi wood which was 0.740 kg /m3. The lowest termites mortality value was in non-teated wood of Sengon wood with value 13.091%, and in other sengon wood which treated by extract of Jati bark with concentration of 2%, 4%, 5%, the termites mortality was 100%. Meanwhile in Sugi wood the termites mortality in non-treated wood was 12.576% and other Sugi wood which treated by extract of Jati bark with concentration of 1%, 2%, 3%, 4%, 5% the mortality value reached 100%. The average percentage values of the highest weight loss was 15.483% in non-treated sugi wood, while the lowest weight loss was in sengon wood which was given 5% extract of teak bark with a concentration of only 2.099%. The optimal concentration of Jati tree bark for wood preservation to Sengon wood was on concentration 25, meanwhile in Sugi wood was on concentration 1%.Keywords: Cryptomeria japonica, ekstrak kulit kayu, Falcataria moluccana, preservation, Tectona grandis